2014
DOI: 10.1016/j.nlm.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of nucleus accumbens dopamine receptor subtypes in the learning and expression of alcohol-seeking behavior

Abstract: These studies examined the roles of dopamine D1- and D2-like receptors within the nucleus accumbens (Acb) in the acquisition and expression of ethanol-induced (2 g/kg) conditioned place preference (CPP) in adult male DBA/2J mice. Bilateral intra-Acb infusions of the D1-like dopamine receptor antagonist SCH23390 (0.05, 0.5 µg/side) or the D2-like dopamine receptor antagonist raclopride (0.5–5.0 µg/side) were administered 30 min before each ethanol conditioning trial (acquisition studies) or before preference te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…It remains unclear how differential activity of D1+ and D1− MSNs contribute to ethanol related behaviors. Activity of D1 receptors are necessary for the acquisition of ethanol conditioned place preference (CPP) (Young et al, 2014) and it has been shown that NMDAR activation in the NAc is necessary for the expression of ethanol CPP (Gremel and Cunningham, 2009) but the distinct contribution of NMDAR function in D1 and D2 MSNs for the expression of ethanol CPP or ethanol drinking is unknown. Much work remains to be done to determine how differential activity of D1 and D2 MSNs modulate ethanol related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear how differential activity of D1+ and D1− MSNs contribute to ethanol related behaviors. Activity of D1 receptors are necessary for the acquisition of ethanol conditioned place preference (CPP) (Young et al, 2014) and it has been shown that NMDAR activation in the NAc is necessary for the expression of ethanol CPP (Gremel and Cunningham, 2009) but the distinct contribution of NMDAR function in D1 and D2 MSNs for the expression of ethanol CPP or ethanol drinking is unknown. Much work remains to be done to determine how differential activity of D1 and D2 MSNs modulate ethanol related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our results are consistent with recent work in mice showing that systemic blockade of D1-like receptors using SCH-39166 impairs ethanol-induced CPP acquisition (Bahi and Dreyer 2012) and further extends those findings to an additional mouse strain and antagonist drug. Recent work using site-specific D1-like receptor manipulations suggests the systemic effect of SCH-23390 might be due to its effects on D1-like receptors in the NAc, as focal infusions of this antagonist into NAc reduced acquisition of ethanol-induced CPP (Young et al 2013). Our finding that SCH-23390 did not significantly impact the development of LiCl-induced CPA acquisition suggests that dopamine D1-like receptors do not mediate aversive motivational learning in our procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of GAL into the PVN has been found to increase extracellular levels of dopamine (DA) in the nucleus accumbens (NAc) while simultaneously lowering levels of acetylcholine (ACh) (Rada et al, 1998). Evidence shows that accumbal DA through the D1 receptor can promote alcohol-induced conditioned place preference (Young et al, 2014) as well as alcohol drinking (Bahi and Dreyer, 2012). In contrast, the cholinergic agonist nicotine reduces operant alcohol self-administration when injected into the NAc (Nadal et al, 1998).…”
Section: Neuropeptides With a Positive Feedback Relationship To Almentioning
confidence: 99%